Biology and population dynamics of Nemipterus mesoprion (Bleeker) off Cochin - Joshi, K K (Indian Journal of Fisheries, 2011)
Biology and population dynamics of Nemipterus mesoprion from the trawling grounds off Cochin were studied. The length weight relationship is Log W=-4.700+2.926 Log L. The major food items were fishes, crustaceans and squids. The estimated length at first maturity was 106mm and the spawning season extends from May to November. The estimated von Bertalanffy parameters were Lâˆ =274.5mm, K= 0.85year-1 and to= -0.01 year. The total mortality, fishing mortality and natural mortality were 3.12, 1.856 and 1.26 respectively. Maximum yield could be 694t at 120% of the present effort but yield increase will be 101% of present. The cod end mesh size has to be doubled to get maximum yield.